Differential impacts of plant growth-promoting bacteria (PGPB) on seeds of neotropical tree species with contrasting tolerance to shade - de Souza, Natália Luiz; Rocha, Sâmela Santos; Narezzi, Nick Tramontina; Tiepo, Angélica Nunes; de Oliveira, André Luiz Martinez; Oliveira, Halley Caixeta; Bianchini, Edmilson; Pimenta, José Antônio; Stolf-Moreira, Renata (Trees (Berlin, West), 2020)
Key message The inoculation of seeds from neotropical tree species with PGPB revealed an active role of inoculant strains in modulating the germination and physiology of seedlings, although the specific responses were subject to specific plant–bacteria and genotype–genotype combinations. Beneficial microbial species encompass different phylogenetic groups, and growth-promoting mechanisms can be direct (nutritional effects) or indirect (resistance against biotic and abiotic stresses). Seed inoculation with plant growth-promoting bacteria (PGPB) can increase the growth and productivity of agricultural crops. However, few studies have been conducted to determine these effects on the seed germination and seedling growth of neotropical tree species. Thus, this study aimed to determine the effects of inoculation with PGPB on the germination, initial development and activities of the enzymes phenylalanine ammonia-lyase and polyphenol oxidase of seedlings of neotropical tree species. Shade-intolerant ( Cecropia pachystachya , Heliocarpus popayanensis and Trema micrantha ) and shade-tolerant tree species ( Cabralea canjerana , Cariniana estrellensis and Trichilia elegans ) were inoculated with different species of PGPB ( Azospirillum brasilense , Bacillus sp. and Azomonas sp.) and allowed to germinate and grow for 45 days under greenhouse conditions. Inoculation of C. pachystachya with all types of PGPB increased the percentage of germinated seeds (GS) and the vigor index (VI), while the mean time to germination (MTG) decreased. The VI of T. micrantha increased in response to Bacillus sp. and Azomonas sp. inoculation. Cabralea canjerana showed a decreased GS and VI and an increased MTG when inoculated with PGPB and increased activity of phenylalanine ammonia-lyase and polyphenol oxidase when inoculated with Azomonas sp. Inoculation of PGPB interfered with seed germination and seedling physiology, and shade-intolerant species were more likely to benefit from inoculation. Inoculation with PGPB can modulate the seed germination patterns of neotropical tree species, with indications that the ecological group may be involved in the magnitude of the response.